The Effect of Good Corporate Governance on Profitability With Firm Size As A Moderating Variable (Study on Food and Beverage Subsector Listed on the IDX for the Period 2021-2024) - Tina Mariana Br Sihole; Eka Yulianti (International Journal of Environmental, Sustainability and Social Science, 2025)
The aim of this study is to analyze the influence of good corporate governance on profitability and to examine the role of firm size as a moderating variable for food and beverage companies listed on the Indonesian stock exchange between 2021 and 2024. The study employs a quantitative approach using descriptive and associative methods. The sample consists of 25 companies selected through purposive sampling, resulting in 100 observations. Secondary data were derived from the companies' annual reports and financial statements and were analyzed using panel regression and moderated regression analysis with EViews 13. The research findings show that an independent commissioners board has no impact on the overall return on assets. Manager ownership and institutional ownership have a positive effect on the return on assets. Firm size does not moderate the influence of an independent supervisory board or manager participation on the return on equity. However, firm size can weaken the impact of institutional investors on the return on assets. These findings demonstrate that the effectiveness of corporate governance is determined by the alignment of management interests and active oversight by institutional investors, and not solely by the independent commissioners board. Companies must improve the quality of substantive oversight and adapt their governance mechanisms to the complexity of their size